Icariin Protects Hippocampal Neurons From Endoplasmic Reticulum Stress and NF-κB Mediated Apoptosis in Fetal Rat Hippocampal Neurons and Asthma Rats - Liu, Jiaqi; Liu, Lumei; Sun, Jing; Luo, Qingli; Yan, Chen; Zhang, Hongying; Liu, Feng; Wei, Ying; Dong, Jingcheng (Frontiers in Pharmacology, 2020)
Icariin is a main component of the Chinese medicinal plant Epimedium brevicornu Maxim, exhibits potent activity against inflammatory diseases. Our previous data demonstrated the valid bioactivity of icariin on mitigating rodent asthma. Endoplasmic reticulum stress and NF-κB pathway were involved in the pathogenesis of asthma. However, it remains poorly defined that whether icariin could inhibit ER stress and NF-κB mediated apoptosis in asthma and further influence the central neural system. Herein, we investigated the effects of icariin on primary cultured fetal rat hippocampal neurons and OVALPS-OVA induced asthma rat model. Asthma rat models were established by ovalbumin (OVA) and lipopolysaccharide (LPS) intraperitoneal injection and OVA inhalational challenge. Within 24 h of the last OVA challenge, lung function was detected by direct airway resistance analysis. Lung tissues were examined for pathological changes. Inflammatory cells counts in bronchoalveolar lavage fluids (BALF) were assessed. ELISA was utilized to evaluate the IL-1β, IL-6, TNF-α and IFN-γ level in serum. Protein expression of BiP and IRE-1α, XBP-1s and phosphorylation-IκBα (p-IκBα), IκBα and p65 as well as Cytochrome c, caspase-3 (cleaved caspase-3) and caspase-9 (cleaved caspase-9) were tested by western blot. Our data showed that oral administration of icariin significantly improved pulmonary function and attenuated inflammatory cells infiltration into the lung, levels of inflammatory cytokines and ER stress related proteins as well as NF-κB were prominently suppressed by icariin. Our results suggested that icariin had an inhibitory effect on airway inflammation and neuroprotective effect on ER stress and NF-κB mediated apoptosis in asthma rats and cultured fetal rat hippocampal neurons, which may provide new mechanistic insights into the asthma prevention and treatment of icariin.